Endothelial dysfunction in children with pyelonephritis - Abaturov, O. Ye.; Vakulenko, L. I.; Kunak, O. V. (Zaporozhye Medical Journal, 2019)
Aim. To study the characteristics of vascular endothelium system functioning as a marker of the balance between endothelium-dependent vasodilation and endothelium-dependent vasoconstriction in children with acute and chronic pyelonephritis. Materials and methods. 39 children with acute and 37 with chronic pyelonephritis aged 11–17 years, without exacerbation of the inflammatory process were examined. The control group consisted of 30 apparently healthy children. Endothelium-dependent vasodilatation test adapted to children was used. Results. In children with acute pyelonephritis, the initial index of the brachial artery diameter did not differ significantly from the norm (3.40 ± 0.19 mm, P > 0.05), while it was significantly less in patients with chronic pyelonephritis (2.20 ± 0.12 mm, P < 0.05). In the phase of maximal vasodilation, the brachial artery diameter index was significantly higher (4.10 ± 0.15 mm, P < 0.05) in patients with acute pyelonephritis, and in patients with chronic pyelonephritis – significantly less than the norm (2.60 ± 0.17 mm, P < 0.05). As a result, the brachial artery diameter increase was significantly less in children with chronic pyelonephritis than in healthy children (8.2 ± 0.2 %, P < 0.05), while it was significantly higher (24.10 ± 0.53 %, P < 0.05) in children with acute pyelonephritis. Linear blood flow velocity at rest was significantly lower than normal (111.80 ± 0.17, P < 0.05) in children with acute pyelonephritis and it was significantly increased (148.70 ± 0.14 cm/s, P < 0.05) in children with chronic pyelonephritis. In the phase of reactive hyperemia, the linear flow velocity was decreased in both groups of patients. Conclusions. Endothelial dysfunction is registered in 17.9 % of acute pyelonephritis and in 64.9 % of chronic pyelonephritis cases in children. Diverging paths are observed: in patients with acute pyelonephritis, activity of vasodilatory agents predominates, and in chronic pyelonephritis - vasoconstrictor agents. Endothelial dysfunction associated with chronic pyelonephritis has the risk of unfavorable course of the disease and requires differential management.